Pengaruh Shalat Dhuha terhadap Kedisiplinan Siswa Kelas VIII MTsN Kota Bogor - Indah, Rossa; Mubarak, Zahid; Hambari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the level of dhuha prayer of students in class VIII MTsN Bogor City, determine the level of discipline of students in class VIII MTsN Bogor City and analyze the effect of dhuha prayer on the discipline of students in class VIII MTsN Bogor City. The research method used in this research is quantitative research. This study uses a population of all VIII grade students of MTsN Bogor City with a sample size of 167 people taken randomly. The instruments used in the study were questionnaires and documentation. The data analysis technique in this study used simple linear regression test analysis with the help of the SPSS 26 application. The results showed that: First, the implementation of dhuha prayer for students in class VIII MTsN Kota Bogor obtained a value in the